Research on static voltage stability enhancement for new energy station based on grid-forming control strategy - Wentao, Sun; Guojing, Liu; Yi, Ge; Quanquan, Wang; Hui, Cai; Xingning, Han; Wenjia, Zhang (Frontiers in Energy Research, 2024)
The advent of novel power systems has given rise to a multitude of safety and stability concerns associated with the integration of emerging energy sources and power electronic equipment. The active support of the grid-forming control strategy represents an effective solution to the voltage and frequency stability issues associated with the weak damping and low inertia inherent to high-ratio new energy systems. Firstly, a static voltage stability index based on critical impedance is proposed for assessment of the static stability margin of a new energy grid-connected system, based on the static voltage stability theory of a traditional single-unit single-load system. Secondly, an analysis is conducted of the control principle of the grid-forming control converter and its impedance characteristics. In conclusion, a method for enhancing the static voltage stability margin of gridconnected new energy stations through parameter control of grid-forming converters is presented.The simulation verification of the single-feed and multi-feed systems demonstrates the efficacy and accuracy of the methodology presented in this study.